Malignant Hemangioendothelioma of Occipital Bone - Agrawal, Amit; Bhake, Arvind; Banode, Pankaj; Singh, Brij Raj (Chinese Journal of Cancer Research; Vol 24, No 2 (June 29, 2012): Chinese of Journal Cancer Research, 2012)
Epithelioid hemangioendothelioma is a rare vascular tumor of bone, and rarely these lesions can present as unique and extremely aggressive tumor. We report a case of highly aggressive epithelioid hemangioendothelioma and discuss the imaging findings. CT brain plain study revealed a poorly-defined, mixed density expansile and lytic lesion involving the occipital bone with extension to the left side with poorly defined trabecula formation. There was significant but irregular enhancement after intravenous administration of contrast material and also marked bone destruction. Microscopic examination of the fine needle aspiration cytology showed a tumor composed of vascular channels lined by plump endothelial cells, which had enlarged hyperchromatic nuclei. In view of the extensive infiltration the patient was submitted for the radiotherapy.